"For Me, It's Having Something Meaningful": Women's Emotional Understandings of Sex and the Sexual Acceptability of Contraception. Issue 4 (4th May 2022) - Dalessandro, Cristen; Thorpe, Rachael; Sanders, Jessica
ABSTRACT: While the sexual acceptability of contraception – or, the impact of contraceptive methods on individuals' sexual experiences – is a growing area of research, less frequently do studies engage the importance of individual emotions around sex when it comes to perceptions of sexual acceptability. Building on Higgins and Smith's model of sexual acceptability and drawing upon insights from the sociology of gender, we used qualitative interview data with 30 women in Utah (USA) to explore the importance of emotional understandings of sex for women's assessments of the sexual acceptability of different contraceptives. Here we posit that emotional understandings of sex are not just individualistic – they are also structured by experiences with sexual partners and broader gendered expectations. This work adds insight into the importance of emotions in sexual acceptability and suggests the need for an amendment to Higgins and Smith's model that reflects the synergistic nature of the micro/individual, meso/interactional, and macro factors related to sexual acceptability. We conclude that assessing the sexual acceptability of contraceptives requires a nuanced multi-level interaction framework.